Estimation of sectoral elasticities of substitution along the international technology frontier - Claudio Baccianti (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Sectoral heterogeneity is crucial to address several economic questions. This paper provides a detailed mapping of sectoral production possibility frontiers, using different nesting structures and levels of aggregation (primary, secondary, tertiary activities and energy-intensive firms). Elasticities of substitution between capital, labour and energy are identified by employing an international multi-sector dataset, accounting for biased technological change and normalising the production function to clusters of observations. Complementarity dominates, with the noteworthy exception of the capital-labour composite, close to Cobb-Douglas. I also present some stylized facts relating substitution elasticities to sectoral characteristics.
urn:nbn:de:bsz:180-madoc-352453
Keywords: C68; O14; O41; Q43; 330; Constant Elasticity of Substitution; Normalisation; Sectoral Disaggregation; Nested CES Structure; Energy Demand